2006
DOI: 10.1016/j.rmed.2006.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory muscle training in persons with spinal cord injury: A systematic review

Abstract: The purpose of this paper was to review the effectiveness of respiratory muscle training (RMT) on respiratory muscle strength and endurance, pulmonary function, quality of life, respiratory complications and exercise performance in persons with spinal cord injury. A MEDLINE (National Library of Medicine, Bethesda, MD, USA) database was used for selection of the literature (from 1980 to November 2004), and relevant references from peer-reviewed articles were retrieved as well. Studies investigating the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 27 publications
4
63
1
2
Order By: Relevance
“…31,32 Consideration should be given to the standardization of peak cough flow as an index to enable future comparison and meta-analyses across studies. An important limitation of this meta-analysis is the inclusion of a few participants with paraplegia in the papers of Van Houtte et al 11 and Litchke et al 15 In any meta-analysis, it is always debatable whether it is better to be broadly inclusive in terms of study selection or to be very selective and specific with the selection of studies to be included. In this paper, we chose to be inclusive to examine the overall question as to whether RMT has a role in tetraplegia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31,32 Consideration should be given to the standardization of peak cough flow as an index to enable future comparison and meta-analyses across studies. An important limitation of this meta-analysis is the inclusion of a few participants with paraplegia in the papers of Van Houtte et al 11 and Litchke et al 15 In any meta-analysis, it is always debatable whether it is better to be broadly inclusive in terms of study selection or to be very selective and specific with the selection of studies to be included. In this paper, we chose to be inclusive to examine the overall question as to whether RMT has a role in tetraplegia.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, if we exclude the Litchke et al 15 The results of this meta-analysis indicate that RMT is able to increase the functional capacity of the lungs as measured by MVV, which may affect quality-of-life outcomes for people with tetraplegia. Van Houtte et al 11 found that significant improvements in MVV following RMT were coupled with significant improvements in respiratory endurance and health-related quality of life, as measured by the Index of Pulmonary Dysfunction. Litchke et al 15 proposed a similar hypothesis regarding the effect of RMT on overall lung function for wheelchair athletes and the potential subsequent effect on the overall quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(6,(8)(9)(10)(11)(12)(13)(14)(15)(16) Those studies have used different methods for overloading inspiratory muscles, such as the use of threshold trainers, resistive trainers or abdominal weights, as well as normocapnic hyperpnea and training protocols involving high or unknown loads. (11)(12)(13) Some studies have included a control group, (2,11,16,17) whereas others have included only a training group or compared the type of training used with that of another protocol. Although two recent systematic reviews have pointed to a few "trends", no evidence of the effectiveness of respiratory muscle training in spinal cord-injury patients has been established.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, many potential interventions like respiratory muscle training [82] still lack supportive evidence with regard to their efficacy and long-term effectiveness.…”
Section: Need For Researchmentioning
confidence: 99%